2019
DOI: 10.1055/s-0039-1695041
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Meniscal Transplant Failure: A Retrospective Cohort Study

Abstract: The purpose of this study was to analyze the effect of obesity and other clinical factors on the outcome of meniscal allograft transplantation (MAT) with transosseous fixation. A retrospective cohort study was performed on patients who underwent a MAT between 2002 and 2017. All the participants had a minimum follow-up period of 24 months. The variables assessed were age at the time of the transplant, side, sex, transplanted meniscus (lateral/medial), body mass index (BMI), smoking status, and previous surgerie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…Other patient factors such as BMI, age, and mechanical axis had no significant effect on the survival rate of the graft in this study. However, according to Jimenez-Garrido et al, 9 patients with obesity had a higher rate of graft failure. In our study, the BMI of the patients was 25.62 6 3.70, which indicated that the patients were in the overweight category but did not have obesity.…”
Section: Discussionmentioning
confidence: 95%
“…Other patient factors such as BMI, age, and mechanical axis had no significant effect on the survival rate of the graft in this study. However, according to Jimenez-Garrido et al, 9 patients with obesity had a higher rate of graft failure. In our study, the BMI of the patients was 25.62 6 3.70, which indicated that the patients were in the overweight category but did not have obesity.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of osteophytes has been found to significantly increase allograft extrusion [16], and increased failure with higher KL scores has been found in patients undergoing combined MAT with ACLR [40]. Higher MAT failure rates have also been found in patients with a BMI > 30 kg/m 2 along with worse functional results [17].…”
Section: Indications and Contraindications For Meniscal Allograft Tra...mentioning
confidence: 99%
“…For example, Zaffagnini et al 23 did not find any significant effect of BMI on PROs, including KOOS, Lysholm, and visual analog scale (VAS), in a cohort of 117 patients at a mean follow-up of 4.0 ± 1.9 years. In contrast, a case-control study by Jimenez-Garrido et al 24 reported that patients with a BMI >30 kg/m 2 had significantly lower IKDC scores, on average about 12 points lower, than nonobese patients. In addition, the obese cohort had significantly higher failure rates, although this outcome measure was not assessed in the present study.…”
Section: Discussionmentioning
confidence: 86%